High-barrier curl-resistant release film
By using a blend of PA6 and nylon MXD6 as a barrier layer in the release film and adding EVOH to the inner layer, the problem of degradation and curling of gas barrier properties in high temperature and humidity environments is solved, and higher barrier properties and longer service life are achieved.
Patent Information
- Application Number
- CN202411871497.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing release films are prone to deterioration of gas barrier properties and curling in high temperature and humidity environments, resulting in a decrease in the bonding strength of self-adhesive asphalt coils, affecting their service life.
The structure of the surface layer, the sub-surface layer, the outer bonding layer, the barrier layer, the inner bonding layer, the sub-inner layer and the inner layer are arranged in sequence from the table to the inside. The barrier layer uses a blend of PA6 and nylon MXD6, and EVOH is added to the inner layer to improve oil resistance and barrier properties.
It effectively improves the gas and water vapor barrier properties of the release film, prevents oxygen infiltration and asphalt oil penetration, extends the service life of self-adhesive asphalt coils, and maintains a bonding strength of more than 98.4% under 70°C.
Smart Images

Figure BDA0005195879000000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of release films, and more specifically, relates to a high-barrier anti-curling release film. Background Art
[0002] During the storage and transportation of self-adhesive asphalt membranes in summer, the temperature of the self-adhesive asphalt membranes can reach 60°C. If the release film does not have a good barrier effect, the asphalt membranes will undergo thermal oxidation aging if stored at this temperature for a long time, causing the bonding strength between the membrane and the substrate to decrease, affecting the service life of the membranes.
[0003] Existing barrier release films are divided into two categories, namely coating type and multi-layer co-extrusion type.
[0004] The coating type is to coat a barrier liquid on one side of the release film, generally polyvinyl alcohol, PVDC, EVOH, etc. This method of producing release film not only increases the production process of the release film, but also polyvinyl alcohol and EVOH are easily hydrolyzed when in contact with water, resulting in barrier failure; PVDC is not environmentally friendly, cannot be recycled, and can easily produce carcinogens such as dioxins when incinerated.
[0005] The multi-layer co-extrusion type is to add a layer of barrier material during the production process, and the barrier material is generally nylon 6. The production process of the multi-layer co-extrusion release film is simple, the materials are easy to obtain, and the cost is controllable.
[0006] but:
[0007] Nylon 6 material is easily affected by air humidity, resulting in a decrease in gas barrier performance. For example, if the release film is stored in a rainy and humid environment in the south for one day, the gas barrier performance of nylon 6 material can be attenuated by more than 50%. This is because nylon 6 material contains amine and carbonyl groups, which easily form hydrogen bonds with water molecules. After absorbing water, the distance between nylon 6 molecular chains becomes larger, forming more micropores and channels, which are conducive to the passage of gas, so the gas barrier performance of the release film is reduced.
[0008] In addition, due to the differences in materials, the release film of the multi-layer co-extruded film will curl toward the surface after being heated, causing the self-adhesive asphalt coil to be directly exposed to the air, which in turn affects the service life of the coil. Among them, the reason why the release film curls toward the surface when heated is that the release film is a multi-layer co-extruded film, the barrier layer is nylon, and the surface and inner layers are polypropylene or polyethylene, and the material properties of each layer are different. Olefin materials have poor oil resistance. After the coil is heated, the movement of oil in the asphalt intensifies, and the aromatic hydrocarbons in the oil can easily penetrate and swell olefins. However, the hydrogen bonds in the molecular structure of nylon are strong and the crystallinity is high, so aromatic hydrocarbons cannot swell nylon, resulting in the inner layer of polypropylene being swollen, and the surface layer of polypropylene is not swollen, so the release film curls outward.
[0009] In summary, the barrier properties of nylon release film decrease, and curling after aging causes the release film to delaminate from the asphalt surface. The two are the main reasons for the decrease in the bonding strength of self-adhesive asphalt membranes. Therefore, there is an urgent need to provide a high-barrier and anti-curling release film whose barrier properties are not affected by environmental humidity, so as to ensure the bonding strength of the asphalt membrane and extend the service life of the asphalt membrane. Summary of the invention
[0010] The purpose of the present invention is to provide a high barrier anti-curling release film in view of the deficiencies of the prior art. The present invention can ensure the bonding strength of the self-adhesive asphalt coil after thermal aging.
[0011] In order to achieve the above object, the present invention provides a high barrier anti-curling release film, the release film comprising a surface layer, a sub-surface layer, an outer adhesive layer, a barrier layer, an inner adhesive layer, a sub-inner layer and an inner layer arranged in sequence from the surface to the inside;
[0012] The material of the barrier layer includes PA6 and nylon MXD6, and / or the material of the inner layer includes homopolypropylene, copolymer polypropylene, EVOH and a compatibilizer.
[0013] According to the present invention, preferably, based on the total weight of the surface layer, the material of the surface layer includes 75% to 85% homopolypropylene, 5% to 15% copolymer polypropylene and 5% to 10% masterbatch.
[0014] In the present invention, except for the barrier layer and the inner and outer adhesive layers, each layer of the release film of the present invention adopts a combination of homopolymer and copolymer polypropylene, wherein the homopolymer is mainly used and the copolymer is supplemented. The main reason is that the homopolymer polypropylene has higher tensile strength and rigidity, and better heat resistance. The temperature of the self-adhesive polymer asphalt waterproofing membrane is relatively high during production, which ensures that the release film will not be wrinkled due to high temperature when it contacts the membrane; the higher tensile strength ensures that the self-adhesive asphalt membrane will not be broken during film tearing and affect the construction during use. Copolymer polypropylene has better toughness, which ensures better adhesion between the self-adhesive asphalt membrane and the membrane during production, and improves the flatness of the membrane surface after the membrane is stored. The better toughness helps to prevent the release film from being torn horizontally during the membrane tearing process. In short, the method of blending homopolymer and copolymer polypropylene can not only ensure the flatness of the membrane surface during production and storage, but also ensure the stability of the membrane tearing process.
[0015] In the present invention, as a preferred embodiment, the masterbatches used in the present invention are all polypropylene carrier masterbatches. By using polypropylene as the carrier, the masterbatches are more compatible with the main material, and it is not easy to have color difference, crystal points, holes and other undesirable appearance phenomena during casting.
[0016] According to the present invention, preferably, based on the total weight of the sub-surface layer, the material of the sub-surface layer comprises 75% to 85% of homopolypropylene and 15% to 25% of copolymer polypropylene.
[0017] According to the present invention, preferably, based on the total weight of the outer bonding layer, the material of the outer bonding layer includes 85% to 100% copolymerized polypropylene and 0% to 15% homopolymerized polypropylene.
[0018] According to the present invention, preferably, based on the total weight of the barrier layer, the material of the barrier layer includes 75-85% PA6 and 15-25% nylon MXD6.
[0019] In the present invention, the viscosity of PA6 is 2 to 5 Pa·s; the viscosity of nylon MXD6 is 2 to 5 Pa·s.
[0020] In the present invention, when the percentage of nylon MXD6 in the barrier layer is 15-25%, the barrier effect and film-forming effect are optimal, and the overall toughness and strength of the material are optimal.
[0021] In the present invention, MXD6 and PA6 (nylon 6) are selected to be blended to increase the barrier property of the release film. This is because the molecular chains of MXD6 are arranged regularly and tightly, and MXD6 has a high degree of crystallinity. The molecules in the crystalline region are arranged tightly and orderly, making it difficult for gas and water vapor molecules to penetrate through. In addition, there are strong hydrogen bonds between MXD6 molecules, which enhances the interaction between molecules and limits the penetration of small molecules.
[0022] In addition, the present invention can also increase the stiffness of the release film and improve the curling of the coil by adding MXD6 nylon material to the barrier layer and blending and modifying the existing nylon 6. This is because: the presence of benzene rings in MXD6 increases the rigidity of the molecular chain, making the material less likely to bend and twist, and the structure of the benzene rings is relatively stable, which can enhance the heat resistance of MXD6, and the higher crystallinity and more regular molecular chain structure of MXD6 also help to improve the material's ability to resist deformation.
[0023] According to the present invention, preferably, based on the total weight of the inner bonding layer, the material of the inner bonding layer includes 85% to 100% copolymerized polypropylene and 0% to 15% homopolymerized polypropylene.
[0024] According to the present invention, preferably, based on the total weight of the secondary inner layer, the material of the secondary inner layer comprises 75% to 85% of homopolypropylene and 15% to 25% of copolymer polypropylene.
[0025] According to the present invention, preferably, based on the total weight of the inner layer, the material of the inner layer includes 20-40% homopolypropylene, 30-40% copolymer polypropylene, 15-25% EVOH, 5-10% compatibilizer and 5-15% masterbatch.
[0026] In the present invention, the mechanism by which EVOH exerts its oil barrier effect is as follows: EVOH molecules contain a large number of hydroxyl groups, which make them highly polar, while asphalt oil is a non-polar substance. The interaction between the two is weak, and oil is not easily adsorbed. In addition, hydroxyl groups easily form hydrogen bonds. This hydrogen bond network makes the EVOH molecular structure relatively compact, and therefore, oil is more difficult to penetrate.
[0027] According to the present invention, preferably, the compatibilizer is PP-g-MAH and / or PE-g-MAH.
[0028] According to the present invention, preferably, the release film is made by a co-extrusion casting process.
[0029] According to the present invention, preferably, the total thickness of the release film is 0.03 mm to 0.1 mm, and the width is 950 mm to 1070 mm.
[0030] According to the present invention, preferably, the thickness ratio of each layer of the release film is: surface layer 10% to 30%, sub-surface layer 15% to 25%, outer bonding layer 5% to 15%, barrier layer 20% to 30%, inner bonding layer 5% to 15%, sub-inner layer 15% to 25%, and inner layer 10% to 30%.
[0031] According to the present invention, preferably, a silicone oil layer is thermally cured or UV cured on one side surface of the inner layer, and the self-adhesive asphalt coil is bonded to the silicone oil layer.
[0032] According to the present invention, preferably, the material of the silicone oil layer is at least one of methyl silicone oil, amino silicone oil, hydrogen-containing silicone oil and vinyl silicone oil.
[0033] According to the present invention, preferably, the coating amount of the silicone oil layer is 0.5 to 1.5 g / mm 2 .
[0034] In the present invention, the surface layer, the subsurface layer, the subinner layer, and the inner layer:
[0035] The melt index of homopolymer polypropylene is 2-5 g / 10 min (230°C, 2.16 kg);
[0036] The melt index of copolymerized polypropylene is 5-10 g / 10 min (230°C, 2.16 kg);
[0037] The melt index of masterbatch is 5-10g / min (230℃, 2.16kg);
[0038] The melt index of EVOH is 5-10 g / min (210°C, 2.16 kg);
[0039] In the present invention, the outer bonding layer and the inner bonding layer:
[0040] The melt index of copolymerized polypropylene is 2-5 g / 10 min (230° C., 2.16 kg).
[0041] The beneficial effects of the technical solution of the present invention are as follows:
[0042] The material of the barrier layer of the present invention is a mixture of PA6 and nylon MXD6. PA6 has excellent gas barrier properties, but PA6 easily absorbs water, resulting in a decrease in gas barrier properties, which affects the service life of the coil. MXD6 has excellent gas barrier properties, and the barrier properties are not affected by humidity. Therefore, the present invention uses a mixture of PA6 and MXD6 to increase the barrier properties of the release film, and the barrier properties are not affected by humidity. It can effectively prevent oxygen infiltration and prevent the self-adhesive asphalt coil from aging and affecting the service life of the coil.
[0043] The release film of the present invention adds 15% to 25% EVOH and 5% to 10% compatibilizer to the inner layer polypropylene and masterbatch, the purpose is to increase the oil resistance of polypropylene, this is because the polypropylene material does not have oil resistance, the self-adhesive asphalt coiled material after being heated, the oil movement in the asphalt intensifies, part of the oil infiltrates and swells the polypropylene, however, nylon has a high oil resistance, the asphalt oil cannot continue to penetrate and swell, resulting in the inner layer polypropylene being swollen, the surface layer polypropylene is not swollen, so the release film curls outward. Therefore, the release film of the present invention adds EVOH with good barrier properties and oleophobicity in the inner layer to prevent asphalt oil from penetrating and swelling the inner layer PP, prevent the release film from curling, and ensure that the self-adhesive asphalt coiled material does not curl when stored at 70°C for seven days. Moreover, the present invention uses PP and EVOH blended in the inner layer, rather than using EVOH alone as a barrier layer, so that it can achieve a good oil barrier effect and reduce the amount of materials used.
[0044] The present invention uses "PA6 and MXD6 mixed" and "EVOH added to the inner layer" to make the release film of the present invention not only block oxygen and water vapor in the air, but also prevent the oil in the asphalt from penetrating outward, better protect the self-adhesive asphalt coil, and extend the service life of the self-adhesive asphalt coil. The release film of the present invention can ensure the bonding strength of the self-adhesive asphalt coil after thermal aging. After aging in a 70°C oven for seven days, the bonding strength can be maintained at more than 98.4% compared with before aging.
[0045] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0046] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0047] Example 1
[0048] This embodiment provides a high barrier anti-curling release film, the release film comprising a surface layer, a sub-surface layer, an outer adhesive layer, a barrier layer, an inner adhesive layer, a sub-inner layer and an inner layer arranged in sequence from the surface to the inside;
[0049] The inner layer has a UV-cured silicone oil layer on one side, and the self-adhesive asphalt coil is bonded to the silicone oil layer; the silicone oil layer is made of methyl silicone oil, and the coating amount of the silicone oil layer is 0.8 g / mm 2 .
[0050] The release film is made by a co-extrusion casting process;
[0051] The total thickness of the release film is 0.03 mm and the width is 1040 mm;
[0052] The thickness of each layer of the release film is as follows: surface layer 18%, sub-surface layer 18%, outer bonding layer 7%, barrier layer 30%, inner bonding layer 7%, sub-inner layer 10%, and inner layer 10%.
[0053] Based on the total weight of the surface layer, the material of the surface layer includes 80% homopolypropylene (Sinopec K8003), 10% copolymer polypropylene (Sinopec M800E) and 10% grey masterbatch (Ningbo Masterbatch).
[0054] Based on the total weight of the sub-surface layer, the material of the sub-surface layer includes 80% homopolypropylene (PetroChina T30S) and 20% copolymer polypropylene (Sinopec K8009).
[0055] Based on the total weight of the outer bonding layer, the material of the outer bonding layer is copolymerized polypropylene (Mitsui Chemicals QF551A).
[0056] Based on the total weight of the barrier layer, the material of the barrier layer includes 85% of PA6 (Yueyang Petrochemical YH3400) and 15% of nylon MXD6 (Sinochem).
[0057] Based on the total weight of the inner bonding layer, the material of the inner bonding layer is copolymerized polypropylene (Mitsui Chemicals QF551A).
[0058] Based on the total weight of the sub-inner layer, the material of the sub-inner layer includes 80% homopolypropylene (PetroChina T30S) and 20% copolymer polypropylene (Sinopec K8009).
[0059] Based on the total weight of the inner layer, the material of the inner layer includes 30% homopolypropylene (Sinopec K8003), 40% copolymer polypropylene (Sinopec M800E), 15% EVOH (ethylene vinyl alcohol copolymer, Mitsubishi D2908), 5% PP-g-MAH (SK Chemical 18732) and 10% black masterbatch (Miaocai).
[0060] Example 2
[0061] The difference between this embodiment and embodiment 1 is only that:
[0062] Based on the total weight of the barrier layer, the material of the barrier layer includes 100% PA6 (Yueyang Petrochemical YH3400).
[0063] Example 3
[0064] The difference between this embodiment and embodiment 1 is only that:
[0065] Based on the total weight of the inner layer, the material of the inner layer includes 40% homopolypropylene (Sinopec K8003), 50% copolymer polypropylene (Sinopec M800E) and 10% black masterbatch (Miaocai).
[0066] Comparative Example 1
[0067] This comparative example provides a release film, and the difference between this comparative example and Example 1 is only that:
[0068] Based on the total weight of the barrier layer, the material of the barrier layer includes 100% PA6 (Yueyang Petrochemical YH3400).
[0069] Based on the total weight of the inner layer, the material of the inner layer includes 40% homopolypropylene (Sinopec K8003), 50% copolymer polypropylene (Sinopec M800E) and 10% black masterbatch (Miaocai).
[0070] Test Case
[0071] This test example tests the release films of the above embodiments and comparative examples.
[0072] The test methods are GB 23441-2009, GB / T 19789-2021, GB / T 25256-2010;
[0073] The test results are shown in Table 1.
[0074] Table 1
[0075]
[0076] Combining the above data, we can see that:
[0077] The addition of MXD6 can greatly improve the oxygen barrier performance of the release film, and the oxygen permeability does not change much with the increase of humidity; and the addition of MXD6 also increases the tensile strength of the release film in the transverse and longitudinal directions.
[0078] Adding EVOH to the inner layer of the release film can effectively improve the curling degree of the release film in a 70°C oven.
[0079] Increasing the barrier properties of the release film or improving the curling degree of the release film can improve the bonding strength of the coil after aging at 70°C. Combining the improvement of the barrier properties and the curling degree, the best bonding strength can be obtained, and the bonding strength decay after aging is less than 1.6%.
[0080] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A high barrier anti-curling release film, characterized in that: The release film comprises a surface layer, a sub-surface layer, an outer adhesive layer, a barrier layer, an inner adhesive layer, a sub-inner layer and an inner layer arranged in sequence from the surface to the inside; The material of the barrier layer includes PA6 and nylon MXD6, and / or the material of the inner layer includes homopolypropylene, copolymer polypropylene, EVOH and a compatibilizer.
2. The high barrier anti-curling release film according to claim 1, wherein: Based on the total weight of the surface layer, the material of the surface layer includes 75% to 85% of homopolypropylene, 5% to 15% of copolymer polypropylene and 5% to 10% of masterbatch.
3. The high barrier anti-curling release film according to claim 1, wherein: Based on the total weight of the sub-surface layer, the material of the sub-surface layer comprises 75% to 85% of homopolypropylene and 15% to 25% of copolymer polypropylene.
4. The high barrier anti-curling release film according to claim 1, wherein: Based on the total weight of the outer bonding layer, the material of the outer bonding layer includes 85% to 100% of copolymerized polypropylene and 0% to 15% of homopolymerized polypropylene.
5. The high barrier anti-curling release film according to claim 1, wherein: Based on the total weight of the barrier layer, the material of the barrier layer includes 75-85% of PA6 and 15-25% of nylon MXD6.
6. The high barrier anti-curling release film according to claim 1, wherein: Based on the total weight of the inner bonding layer, the material of the inner bonding layer includes 85% to 100% of copolymerized polypropylene and 0% to 15% of homopolymerized polypropylene.
7. The high barrier anti-curling release film according to claim 1, wherein: Based on the total weight of the sub-inner layer, the material of the sub-inner layer includes 75% to 85% of homopolypropylene and 15% to 25% of copolymer polypropylene.
8. The high barrier anti-curling release film according to claim 1, wherein: Based on the total weight of the inner layer, the material of the inner layer includes 20-40% homopolypropylene, 30-40% copolymer polypropylene, 15-25% EVOH, 5-10% compatibilizer and 5-15% masterbatch; Preferably, the compatibilizer is PP-g-MAH and / or PE-g-MAH.
9. The high barrier anti-curling release film according to claim 1, wherein: The release film is made by a co-extrusion casting process; The total thickness of the release film is 0.03 mm to 0.1 mm, and the width is 950 mm to 1070 mm; The thickness of each layer of the release film is as follows: surface layer 10% to 30%, sub-surface layer 15% to 25%, outer bonding layer 5% to 15%, barrier layer 20% to 30%, inner bonding layer 5% to 15%, sub-inner layer 15% to 25%, and inner layer 10% to 30%.
10. The high barrier anti-curling release film according to claim 1, wherein: A silicone oil layer is formed on one side of the inner layer by heat curing or UV curing, and the self-adhesive asphalt coil is bonded to the silicone oil layer; Preferably, the material of the silicone oil layer is at least one of methyl silicone oil, amino silicone oil, hydrogen silicone oil and vinyl silicone oil; Preferably, the coating amount of the silicone oil layer is 0.5 to 1.5 g / mm 2 .
Citation Information
Patent Citations
Modified polypropylene film for backside adhesive bag and preparation method thereof
CN101844643A
Nylon-6-modified polypropylene composite release film and processing method thereof
CN106346925A
Research and development of 15g light-stripping yellowing-resistant isolating membrane
CN111993730A
Antistatic enhanced hot melting connection pipe fitting and pipe fitting hot melting connection structure
CN213402338U
Multilayered film
JP1995241964A